Ziphius cavirostris G. Cuvier 1823 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
3. Cuvier’s Beaked Whale Ziphius cavirostris French: Baleine-a-bec de Cuvier / German: Cuvier-Schnabelwal / Spanish: Zifio de Cuvier Other common names: Goose-beaked Whale, Goosebeak Whale Taxonomy. Ziphius cavirostrnis G. Cuvier, 1823, France, “dans le département des Bouches-du-Rhone, entre de Fos et I’embouchure du Galégeon” (= between Fos and the mouth of the Galégeon River). No subspecies are currently recognized, but further research may reveal genetic differences between populations in different ocean areas. Monotypic. Distribution. All warm temperate to tropical waters of the world and perhaps in cooler waters in the Southern Ocean and the N Pacific Ocean. It is the only species of beaked whales that commonly occurs in the Mediterranean Sea. Descriptive notes. Total length 600-700 cm; weight 2500-3500 kg. Body of Cuvier’s Beaked Whale is spindle-shaped, with greatest girth around its midpoint. Flukes are wide in relation to body length, and tailstock is compressed laterally. Dorsalfin is small and set approximately two-thirds the distance between tip of the beak and end of the tail. Coloration is typically dark brown or dark gray. Adults of both sexes may have paler heads. In adult males, the pale head is usually very distinct, and a pale patch extends backward from it as far as the dorsal fin. Dorsal surface of adult males may also be covered in pale linear scars that are concentrated between head and dorsal fin. Rostrum and lower jaw form a short beak that is barely distinguishable from the bulbous forehead; there are two grooves on the throat. Adult males have a pair of conical tusksat the tip of the lowerjaw that may become worn down as far as the gums in older individuals. Habitat. Deep, oceanic waters and generally in areas where water depths are more than 500 m. Cuvier’s Beaked Whales appearto favor areas with complex seabed topography and are most commonly recorded in canyons along the shelf margins, around oceanic islands, or around seamounts. Food and Feeding. Cuvier’s Beaked Whales primarily ...